Combined accelerated collagen crosslinking and sub-Bowman's keratomileusis in high myopic eyes: a comparison between total ultraviolet energy dose. (4th July 2022) - Wan, Kelvin H; Chan, Tommy CY; Kwok, Peter SK; Ng, Alex LK
ABSTRACT: Aim: To compare the safety, efficacy, and predictability outcomes of combined sub-Bowman's keratomileusis (thin flap laser in situ keratomileusis [LASIK]) and accelerated crosslinking (CXL) using two different irradiation durations. Methods: A retrospective comparative study of patients with percent tissue altered ≥35%, undergoing simultaneous CXL during sub-Bowman's keratomileusis were recruited. Following riboflavin application, they underwent ultraviolet-A (UVA) irradiation (18 mW/cm 2 ) for either 2 min (total energy 2.16 J/cm 2 ) or 3 min (total energy 3.24 J/cm 2 ). Visual and refractive outcomes were compared between follow-up visits during the first year postoperatively. Demarcation line and endothelial cell count were evaluated, respectively, at 1 and 3 months postoperatively. Results: The baseline characteristics were similar between the 40 eyes/patients treated using the 2-min protocol and the 33 eyes/patients treated with the 3-min protocol ( p ≥ .114). Uncorrected distance visual acuity and corrected distance visual acuity were significantly better for eyes treated with the shorter irradiation protocol on Day 1 ( p ≤ .030) and Month 1 ( p ≤ .040) postoperatively; these differences diminished by Month 3 ( p ≥ .070). Likewise, the efficacy index was higher during the first postoperative week for the 2-min protocol ( p ≤ .043). At 1 year, the proportion of eye attaining within 0.5 D of target refraction was 80.0% and 84.8% for the 2-min and 3-min protocols, respectively ( p = .590). The corresponding corneal stromal demarcation line depth and endothelial cell density changes were comparable between the two groups ( p = .311 and 0.899, respectively). Conclusions: A comparable volume of crosslinked corneal tissue can be achieved by using a shorter UVA irradiation duration. Additional duration of UVA irradiation could lead to delay in visual rehabilitation after simultaneous sub-Bowman's keratomileusis and CXL.